Insight into the mobilome of Aeromonas strains - Piotrowska, Marta; Popowska, Magdalena (Frontiers in Microbiology, 2015)
The mobilome is a pool of genes located within mobile genetic elements (MGE), such as plasmids, IS elements, transposons, genomic/pathogenicity islands, and integron-associated gene cassettes. These genes are often referred to as "flexible" and may encode virulence factors, toxic compounds as well as resistance to antibiotics. The phenomenon of MGE transfer between bacteria, known as horizontal gene transfer (HGT), is well documented. The genes present on MGE are subject to continuous processes of evolution and environmental changes, largely induced or significantly accelerated by man. For bacteria, the only chance of survival in an environment contaminated with toxic chemicals, heavy metals and antibiotics is the acquisition of genes providing the ability to survive in such conditions. The process of acquiring and spreading antibiotic resistance genes (ARG) is of particular significance, as it is important for the health of humans and animals. Therefore, it is important to thoroughly study the mobilome of Aeromonas spp. that is widely distributed in various environments, causing many diseases in fishes and humans. This review discusses the recently published information on MGE prevalent in Aeromonas spp. with special emphasis on plasmids belonging to different incompatibility groups, i.e., IncA/C, IncU, IncQ, IncF, IncI and ColE-type. The vast majority of plasmids carry a number of different transposons (Tn3, Tn21, Tn1213, Tn1721, Tn4401), the 1st, 2nd or 3rd class of integrons, IS elements (e.g. IS26, ISPa12, ISPa13, ISKpn8, ISKpn6) and encode determinants such as antibiotic and mercury resistance genes, as well as virulence factors. Although the actual role of Aeromonas spp. as a human pathogen remains controversial, species of this genus may pose a serious risk to human health. This is due to the considerable potential of their mobilome, particularly in terms of antibiotic resistance and the possibility of the horizontal transfer of resistance genes.